2018
DOI: 10.1002/bmb.21176
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions and persistence: resources for targeting student alternative conceptions in biotechnology

Abstract: Conceptual understanding and reasoning of nonscience major students enrolled in a course on biotechnology were evaluated before and after instruction. The instrument for analysis of student understanding was the Biotechnology Instrument for Knowledge Elicitation (BIKE). The BIKE targets 11 key concepts, as determined by experts in the field. A statistically significant score improvement was observed in each of the 11 concept areas after completion of the course, Biotechnology in Society (N = 117). Student resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…A number of these concepts differ from conventional scientific views. These incorrect concepts are called naïve ideas (e.g., Pine, Messer, & St. John, 2001), alternative conceptions (e.g., Adadan, Trundle, & Irving, 2010;Prokop, Prokop, & Tunnicliffe, 2008b), misconceptions (e.g., Treagust, 1986;Wandersee, 1986), or both alternative conceptions and misconceptions (Wisch, Farrell, Siegel, & Freyermuth, 2018) (for discussion regarding the use of the term misconception see Leonard, Andrews, & Kalinowski, 2014). They have become one of the possible reasons for student's difficulties in the learning process, because they can interfere with the acquisition of new knowledge (Hadzigeorgiou, 2015;Vosniadou, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A number of these concepts differ from conventional scientific views. These incorrect concepts are called naïve ideas (e.g., Pine, Messer, & St. John, 2001), alternative conceptions (e.g., Adadan, Trundle, & Irving, 2010;Prokop, Prokop, & Tunnicliffe, 2008b), misconceptions (e.g., Treagust, 1986;Wandersee, 1986), or both alternative conceptions and misconceptions (Wisch, Farrell, Siegel, & Freyermuth, 2018) (for discussion regarding the use of the term misconception see Leonard, Andrews, & Kalinowski, 2014). They have become one of the possible reasons for student's difficulties in the learning process, because they can interfere with the acquisition of new knowledge (Hadzigeorgiou, 2015;Vosniadou, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One way to detect these disorders is to intravitally diagnose metabolic disorders with the help of morphological and biochemical E3S Web of Conferences 164, 06020 (2020) TPACEE-2019 https://doi.org/10.1051/e3sconf /202016406020 blood indicators. These studies are particularly important in assessing the effects of new fodder substances [5][6][7].…”
Section: Morphological and Biochemical Blood Indicatorsmentioning
confidence: 99%
“…For many microorganisms, the effectiveness of biological detoxification of metals through targeted microbial activity depends on factors such as the age of culture, the cell shape, pH, contact time, and initial concentrations of metals in the solution [6]. In this regard, several studies with actively growing cells showed that some microorganisms could effectively remove heavy metal ions from the nutrient environment, especially when the concentration of metals was relatively low [7].…”
Section: Introductionmentioning
confidence: 99%